Evaluasi Program Sosialisasi Civic Literacy Dalam Pembentukan Etika Warganegara Muda - Armaidy Armawi; Raharjo Raharjo (Jurnal Filsafat "WISDOM", 2021)
This study aims to find out and evaluate the process of civic literacy socialization to establish the ethics of young citizens and the implications towards personal resilience in Surakarta and formulating the socialization model of civic literacy as a form of citizenship education.This research was conducted in Surakarta with the target of community conducting citizenship education activities. This research used field research with descriptive qualitative approach which describes citizenship education practice which is done informally in socialization of civic literacy activities. The results showed that the socialization of civic literacy was done informally with habituation, development, and learning which was done continuously and had the objective to form the ethics of citizens with the perspective of personal resilience. This research also produces a model of civic literacy as a planning in the learning process which contains information about how to be an ethical citizen, understand the rights and obligations, have a sense of responsibility and nationalism that is implemented in the life of society, nation and state.